Beach erosion aggravates the drastic decline in marine turtle populations in French Guiana - Damien Chevallier; Marc Girondot; Christina Péron; Jordan Martin; Marc Bonola; Johan Chevalier; Benoît de Thoisy; Laurent Kelle; Yvon Le Maho; Antoine Gardel; Edward J. Anthony (Regional Environmental Change, 2023)
Yalimapo beach, near the Maroni River estuary in French Guiana, is an important turtle nesting site. The interaction of massive mud banks migrating alongshore from the distant Amazon River with discharge from the Maroni River generates strong beach morpho-sedimentary changes. The eventual degradation of the marine turtle nesting habitats resulting from these changes represents a threat to the offspring, and consequently, to the turtle population. Field operator counts of green and leatherback turtle nests were combined with high-resolution topographic measurements of the beach over four field surveys in 2012 and 2014 to map the topographic modifications susceptible to affect nesting on Yalimapo beach. We assumed that the survival of nests was at stake when the depth of sand between the egg chamber and the topographic surface (i.e. the top) of the beach was < 50 cm, and that beach surface lowering > 10 cm represented unfavourable conditions for nest safety with unequal nest survival across the beach. Erosion of the beach surface exceeding a depth of 50 cm therefore results in nest destruction. Digital elevation models were produced to quantify the topographic modification of nesting on Yalimapo beach and highlight the endangered nesting areas. As the modification of the beach is not linear, some sectors are more eroded than others, resulting in unequal nest survival across the beach. Overall, up to 40% of the nests were presumed destroyed over the 2 years of survey, but true losses would depend on the species and the preferential locations of their nesting habitats. The relatively unfavourable conditions that prevailed during the 2 years of the survey are consistent with persistent erosion of Yalimpao beach since 2011. This ongoing erosion could explain in part the drastic decline of the leatherback turtle population in western French Guiana over the period 2001–2018. The substrate quality and dynamics of the nesting beach in relation to the preferred nesting habitat of each species are therefore critical issues that should be considered in the conservation strategies of marine turtles. The beach nesting conditions of marine turtles in French Guiana, as elsewhere, could be further aggravated in the future by climate change effects, including sea-level rise.

Subcellular architecture and metabolic connection in the planktonic photosymbiosis between Collodaria (radiolarians) and their microalgae - Johan Decelle; Giulia Veronesi; Charlotte LeKieffre; Benoit Gallet; Fabien Chevalier; Hryhoriy Stryhanyuk; Sophie Marro; Stéphane Ravanel; Rémi Tucoulou; Nicole Schieber; Giovanni Finazzi; Yannick Schwab; et al. (Environmental Microbiology, 2021)
Summary Photosymbiosis is widespread and ecologically important in the oceanic plankton but remains poorly studied. Here, we used multimodal subcellular imaging to investigate the photosymbiosis between colonial Collodaria and their microalga dinoflagellate ( Brandtodinium ). We showed that this symbiosis is very dynamic whereby symbionts interact with different host cells via extracellular vesicles within the colony. 3D electron microscopy revealed that the photosynthetic apparatus of the microalgae was more voluminous in symbiosis compared to free‐living while the mitochondria volume was similar. Stable isotope probing coupled with NanoSIMS showed that carbon and nitrogen were stored in the symbiotic microalga in starch granules and purine crystals respectively. Nitrogen was also allocated to the algal nucleolus. In the host, low 13 C transfer was detected in the Golgi. Metal mapping revealed that intracellular iron concentration was similar in free‐living and symbiotic microalgae ( c . 40 ppm) and twofold higher in the host, whereas copper concentration increased in symbionts and was detected in the host cell and extracellular vesicles. Sulfur concentration was around two times higher in symbionts (chromatin and pyrenoid) than their host. This study improves our understanding on the functioning of this oceanic photosymbiosis and paves the way for more studies to further assess its biogeochemical significance.

Meiofauna versus macrofauna as a food resource in a tropical intertidal mudflat - Pierre-Yves Pascal; Pierrick Bocher; Christel Lefrançois; Hien T. Nguyen; Johan Chevalier; Christine Dupuy (Marine Biology, 2019)